Effects of Rehabilitative Therapy in Charcot-Marie-Tooth Disease - Dincher, Andrea (New Advances in Medicine and Medical Science Vol. 4, 2023)
Background: Charcot-Marie-Tooth disease is not yet curable. Symptoms are treated with splints/ orthoses or with physical exercise therapy. So this chapter aims to present the existing methods and their effectivity. Methods: The existing reviews and meta-analyses are summarized and their findings (only RCTs) are shown as standardized mean differences SMD in forest plots, sorted by symptoms. Results: Effect sizes range from SMD = 0.19 on gait, favoring control group (endurance training) to SMD = 0.80 on gait, favoring experimental group (balance training). Conclusions: Strengthening and endurance training only show small effects on Charcot-Marie-Tooth symptoms. Balance training seems to be the most effective.